The West in the world a history of western civilization - Sherman, Dennis; Salisbury, Joyce E. (McGraw Hill Education, 2014)
"'The West in the World,' Fifth Edition, prompts students to take an active, analytical approach to understanding history and historical change. Readers will come to appreciate that history does not happen in isolation but rather is the consequence of a complex set of intersecting events, forces, and human actions among which there are cause-and-effect links that extend into the present day. As it compellingly tells the story of Western civilization, 'The West in the World' encourages a critical examination and analysis of major events and themes. The fifth edition retains the medium length of previous editions, long enough to present a comprehensive, rich narrative but concise enough to give instructors the flexibility to supplement reading with other sources and books. The fifth edition of 'The West in the World' includes the exciting addition of LearnSmart and SmartBook, McGraw-Hills online adaptive learning and reading systems. LearnSmart and SmartBook are the only adaptive learning programs proven to improve performance. LearnSmart and SmartBook help students study more efficiently and retain more knowledge, allowing instructors to focus valuable class time on higher-level concepts."